Penelusuran Informasi Lulusan Sastra Indonesia (Studi Kasus: Tracer Study) - Karbela, Ranisa; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
Abstract The writing of this paper aims to describe the profile of Indonesian Literature Study Program graduates at Padang State University, and describe the success of Indonesian Literature graduates viewed from their profession and income, and describe the opinions of Indonesian Literature graduates in terms of academic services while studying at Padang State University.This type of research is quantitative research. Data was collected using a questionnaire. The location of this research was carried out on the google from application or social media. The object of the study was Indonesian Literature alumni who responded to 71 alumni. Data collection techniques by sharing the link https://forms.gle/UThrexUYVvkmb13q9 questionnaire through WhatshApp media. Data analysis is done using the google from application. Based on the results of the study concluded as follows. First, the profile of graduates of the Indonesian Literature Study Program at Padang State University can be seen from the number of respondents who responded to the questionnaire that had been distributed, the number of alumni in the last 5 years was 240 alumni, while those who responded were only 71 alumni, and the most common among women, and on average to get the first job alumni only takes 3-6 months. Secondly, the success of Indonesian Literature graduates seen from the profession and alumni income from the results of the study proved that many respondents worked while entrepreneurship, and on average the respondents answered the knowledge that jobs with education obtained were not in the field of work, and the salary for the first job received by respondents on average it reaches Rp. 1,000,000-2,000,000. Third, the opinion of Indonesian Literature graduates in terms of academic services during their education at Padang State University, the respondents' opinions on academic services as well as service delivery and overall service quality assessment of aspects of teaching and learning are quite good, such as disciplinary knowledge, knowledge competencies outside the field of science , general knowledge competencies, information technology mastery skills, and others.Keywords: search, information, alumni, Indonesian literature